Investigating performance of full-cell using NaFe0.45Cu0.05Co0.5O2 cathode and hard carbon anode - Van Nguyen , Hoang; Nguyen, Minh Le; Tran, Phuong Hue; Tran, Man Van; Le, Phung My Loan (Vietnam Journal of Science and Technology, 2022)
We evaluated methods aimed at improving the performance of full-cell including: i) Presodiating HC by discharging to 0.1 V in half-cell; ii) Presodiating HC by contacting with Na metal; iii) Activating by low current charging at a rate of C/20 initially, iv) Constant current charging to a cutoff voltage of 3.95 V then hold the voltage for 6 hours. The results showed that the cell being charged by low current density did not exhibit feasible work while the cell (iv) displayed an improvement in capacity while the cell (i) and the cell (ii) both are better in terms of Coulombic efficiency.